An Ammonium Solvate Ionic Liquid. Issue 2 (17th February 2021) - Kawata, Kio; Kitada, Atsushi; Fukami, Kazuhiro; Saimura, Masayuki; Nagata, Takashi; Katahira, Masato; Murase, Kuniaki
Abstract : The first example of ammonium (NH4 + ) solvate ionic liquids (ILs) is reported. The compound is ammonium bis(trifluoromethylsulfonyl)amide-18-crown-6 (1/1), i.e. [NH4 + ][Tf2 N – ]−18C6 (1/1), where Tf represents SO2 CF3 . Raman spectra, NMR spectra, and DFT calculations support the conclusion that the compound can be described as an ammonium solvate IL [NH4 + ·18C6][Tf2 N – ], which consists of 18C6-coordinated NH4 + cations and Tf2 N – anions. The conductivity of the ammonium solvate IL reaches as high as 10 mS cm –1 at 150 °C. The negligible volatility below 200 °C is confirmed by thermogravimetry. Compared with a hydronium (H3 O + ) solvate IL [H3 O + ·18C6][Tf2 N – ], the ammonium solvate IL shows better thermal stability, which strongly suggests long residence time of 18C6 with NH4 + cation. The stability may lead to the vehicular-type translational motions of NH4 + cations with 18C6 solvents as proved by their self-diffusion coefficients. The findings regarding this ammonium solvate IL can provide the guidelines to design new NH4 + or proton conductors for ammonium ion batteries and fuel cells, which work at medium-low temperatures of 150 °C–200 °C.